The Foundation and Nature of Traditional African Morality: A Review of Selected Literature. - Richmond Osei Amoah; Augustine Kojo Peprah (E-Journal of Humanities, Arts and Social Sciences, 2022)
A plethora of questions are asked when discussing moral issues concerning traditional African societies. Common among them are, is African morality dependent on religion only or has its foundation solely on the society, and what is the nature of the traditional African morality? These questions when answered would solve the myriad of ethical issues inherent in the African Traditional Religion. This article looks at the foundation and the nature of traditional African morality. The article establishes theocentric, communalistic, anthropocentric, utilitarian and shame-oriented as the nature of the traditional African morality. It fills the gap that both God and humanity are the foundations of African morality. The authors reviewed selected literature from various scholars. The paper also affirms that God and human society are the foundation of traditional African morality. It recommends that the theocentric and anthropocentric elements of African ethics must be brought together to have a true nature and source of the traditional African morality. This article seeks to contribute to the debate on the nature and foundation of traditional African morality.